2023
DOI: 10.3390/w15122234
|View full text |Cite
|
Sign up to set email alerts
|

An Alternating, Current-Induced Electromagnetic Field for Membrane Fouling and Scaling Control during Desalination of Secondary Effluent from Municipal Wastewater

Abstract: Membrane treatment of secondary effluent for reuse applications is a promising approach to expand water supplies and provide flexibility to water resources management. However, effective control of membrane fouling and scaling is crucial for cost-effective treatment and system resilience. This study compared the performance of antiscalants to an alternating, current-induced electromagnetic field (EMF) as an alternative pretreatment method to reverse osmosis. Compared to the no-EMF control experiments, the EMF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…For concentrates containing high CaSO 4 , suitable scale inhibitors were selected from the following three aspects: Ca 2+ concentration in the concentrate, macroscopic scaling amount, and microscopic CaSO 4 precipitation morphology. RO-400, being the preferred scale inhibitor, shows an effective inhibition effect across a wide range of SIg (2.3-6) and pH (5)(6)(7)(8)(9)(10)(11) values. In the UVD process, a 40 W UV light with 70 mg/L H 2 O 2 can degrade RO-400 completely in 15 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For concentrates containing high CaSO 4 , suitable scale inhibitors were selected from the following three aspects: Ca 2+ concentration in the concentrate, macroscopic scaling amount, and microscopic CaSO 4 precipitation morphology. RO-400, being the preferred scale inhibitor, shows an effective inhibition effect across a wide range of SIg (2.3-6) and pH (5)(6)(7)(8)(9)(10)(11) values. In the UVD process, a 40 W UV light with 70 mg/L H 2 O 2 can degrade RO-400 completely in 15 min.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary reverse osmosis (SRO) can further treat the salt-containing concentrate to reduce the amount of high-concentration brine. The two-stage RO process integrating RO desalination with intermediate concentrate demineralization (ICD) is one of the promising strategies to overcome the recovery limitation caused by mineral scaling during RO desalination [6][7][8][9][10][11]. ICD can reduce the concentration of calcium sulfate in the RO concentrate, allowing it to be further desalted in a subsequent SRO process [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…Cao [31] used a variable-frequency electric field as a pretreatment process for seawater treatment by RO, and the solute rejection and permeate flux were increased by 15-35%, respectively, and the pollutants adhering to the membrane surface were also relatively reduced. Similarly, Penteado de Almeida [32] applied an AC-induced electromagnetic field (EMF) to RO wastewater treatment. The system achieved a 13% increase in the recovery rate, along with a 2-8 times reduction in the scaling rate.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that EMF is an environmentally friendly, non-chemical treatment that minimizes chemical usage, reduces cost (saving time, money, and manpower), and is easy to install with no maintenance and low or no energy consumption [31,32]. It is anticipated that EMF could improve nutrient uptake, plant yield, water efficiency, and soil desalination [31][32][33][34][35]. Studies showed positive effects of EMF-treated synthetic saline irrigation water on plant yield [28,29] and seed germination [36] when different types of EMF devices were used.…”
Section: Introductionmentioning
confidence: 99%